Сервис-ориентированная архитектура и архитектура, управляемая моделями - Карпенко, С.В.; Ткалич, О.П.; Андрухович, П.А. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім.Г.Є.Пухова НАН України, 2010)
In the article the service-oriented architecture (SOA) manageable with the help of the models is described. The main concepts of SOA are discussed. The main aspects and advantages of implementation of SOA in organizations of different types are shown. In comparison the Model-driven architecture concepts of creation of organization model are described.